Indigenous movements and education in the 20th century in the southern Andean region of Puno, Peru - Ruelas Vargas, David (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2019)
This research examines the events that occurred in in the Andean state of Puno in southern Peru with the many indigenous movements of the twentieth century, whose intention was to recover their lands and confront gamonalism.  To this purpose, they met in assemblies and organized protests and marches. Because gamonales and political and religious authorities did not allow schools in the Andean areas, the indigenous population was clandestinely educated in hidden schools run by Quechua and Aymara-speaking indigenous teachers who, among others, intensified the teaching of Spanish despite the prohibition of books in this language. Indigenous education became the only instrument of liberation available against the abusive and exploitative system of semi-feudal servitude of gamonalism. The central aim of this study was to identify these indigenous movements and their struggle for education. The method was qualitative with historical design and was based on the identification of primary and secondary sources for subsequent interpretation. It was possible to conclude that, as a result of the worldwide demand of wool during the 20th century, the gamonales decided to establish themselves in extensive ranches that they obtained after despoiling the indigenous people of the southern Peruvian Andean region of their lands and cattle. This system allowed them to consolidate their political, economic and ecclesiastical control. Several rebellions broke out against them in different sectors, some of the most outstanding uprisings were those of Juan Bustamante, Teodomiro Gutiérrez Cueva, and Wancho Lima. The decision to create clandestine rural schools by the indigenous peoples was not only a way of emancipation but also the road to the recognition of their fundamental rights and their introduction to the international market.